Spatial Distribution and Dietary Risk Assessment of Aflatoxins in Raw Milk and Dairy Feedstuff Samples from Different Climate Zones in China - Xueli Yang; Bolin Liu; Lei Zhang; Xiaodan Wang; Jian Xie; Jiang Liang (Toxins)
This study aimed to explore the contamination of aflatoxins by investigating the spatial distribution of aflatoxin B1 (AFB1) in cow feedstuff and aflatoxin M1 (AFM1) in raw milk, and the potential health risks of AFM1 in milk and dairy products. Feedstuff and raw milk were collected from 160 pastures in three climate zones of China from October to November 2020. The results indicated the level of AFB1 and AFM1 ranged from 51.1 to 74.1 ng/kg and 3.0 to 7.0 ng/kg, respectively. Spatial analysis indicated the contamination was mostly concentrated in the temperate monsoon climate zone. On average, the estimated dietary exposure to AFM1 from milk and dairy products for Chinese consumers ranged from 0.0138 to 0.0281 ng/kg bw/day, with the MOE values below 10,000, and liver cancer risk of 0.00004–0.00009 cases/100,000 persons/year. For different groups, the average exposure to AFM1 was highest in the temperate monsoon climate zone and for toddlers.